The behavioural ecology of reintroduced lions and cheetahs in the Phinda resource reserve, Kwazulu-natal, South Africa - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2013)
Thesis (PhD (Zoology))--University of Pretoria, 2007.